Green Innovation and Firm Performance: A Systematic Literature Review - Khaq, Akhsanul; Anggaredho, Panji Patra; Akbar, Bahrullah; Sunyoto, Edi (KnE Social Sciences, 2025)
The rise of industrialization has brought significant side effects, notably climate change and global warming. In response, green innovation has emerged as a crucial strategy for industrial firms to mitigate these negative environmental impacts. However, many firms, particularly in developing countries, perceive green innovation as offering limited benefits to their performance, leading to its underutilization. This study systematically reviews the literature on green innovation and firm performance, aiming to clarify the definitions, dimensions, and relationship between these two variables. Data were collected from peer-reviewed articles published between 2014 and 2024 in reputable databases such as Emerald and ScienceDirect. The findings reveal the following: (1) Definition: green innovation is defined as environmentally oriented process and product, while the definition of firm performance varies considerably; (2) Dimensions: green innovation is commonly categorized into Green Process Innovation and Green Product Innovation, while profitability is the most frequently used indicator of firm performance; (3) Relationship: the majority of studies find a positive relationship between green innovation and firm performance, although some report that green process innovation may negatively affect firm performance.